Efficacy of acupoint-related therapies for nausea and vomiting in pregnancy: a Bayesian network meta-analysis - Liu, Hejing; Liao, Cai; Deng, Junyuan; Yang, Yunhao; Yang, Yan; Guo, Xiao; Liu, Chunshan; Tang, Chenglin (Frontiers in Medicine, 2025)
ObjectiveBayesian network meta-analysis was used to compare the efficacy of different acupoint-related treatments for Nausea and Vomiting of Pregnancy (NVP).MethodsPubMed, Embase, Cochrane Library, CNKI, Wan Fang, and VIP databases were systematically searched from the time of library construction to February 20, 2025, to include randomized controlled trials (RCTs) comparing acupoint-related treatments for the treatment of nausea and vomiting in pregnancy. Literature screening, data extraction and risk of bias assessment were performed independently by two investigators, Bayesian network Meta-analysis was performed by R4.4.1 software.ResultA total of 38 studies containing 1,164 patients were included, this Bayesian network meta-analysis assessed the efficacy of various treatments for NVP across multiple outcomes. Results indicated that Acupoint Application (AA), Acupressure, Auriculotherapy Acupoint Application (ATAA), Ginger Moxibustion Acupoint Application (GMAA), and Moxibustion Acupoint Application (Mox_AA) were significantly more effective than Press Needle (PN) in improving PUQE scores. Thunder Fire Moxibustion (TFM) ranked highest in efficacy (89.1%), followed by GMAA (74.2%) and Acupressure (70.3%). Regarding overall efficacy, AA was less effective than AA_WA (OR = 0.22) and Acupuncture (OR = 0.44), but more effective than usual care (UT) (OR = 3.76), with AA_WA ranking highest (84.7%). In terms of NVP quality of life, TCM_acupuncture showed the greatest benefit (MD = 30.43), significantly outperforming AA (MD = −42.54), Mox_AA, and UT. Overall, TCM_acupuncture emerged as the most effective treatment for both symptom relief and quality of life improvement, followed by Mox_AA and ATAA, while UT was the least effective across all measures.ConclusionOverall, the analyses showed that TFM may be the most effective in treating NVP, followed by GMAA and ear pressure therapy. Compared to PN, AA, auricular pressure therapy, ATAA and GMAA were more effective. AA was more effective than UT, but not as effective as AA_WA and acupuncture. In terms of quality-of-life improvement, TCM_acupuncture may be the most effective, followed by Mox_AA and ATAA, and UT was the least effective. Overall, acupuncture-based treatments, especially Thunder Fire Moxibustion and TCM acupuncture, performed better in the treatment of NVP.